PENGUJIAN TIANG KAYU DARI LAMPUNG - Suparman Karnasudirdja (Jurnal Penelitian Hasil Hutan, 1986)
The paper presents test results of 50 wooden poles from logged-over forest of Lampung, Owing to difficulty in obtaining pole materials for the test, the number of pole samples tested were below the ASTM D-1036 requirement. The data, however, is expected to be useful for comparing field test result with those obtained from small specimen in the laboratory, which has been used as a basis for evaluating timber suitability for pole material. The results show that the location of failure in 41 out of 50 pole tested as simple cantilever occur near pole tip, where the pole diameter were between 1.11 to 1.40 times pole diameter where the load is applied. In the remaining 9 poles, the maximum fiber stress occur around the ground line. The results also show that wood density had no significant effect on pole strength. This is in contrast with that commonly obtained in a laboratory test, in which strength is generally related to wood density. Using pole circumference data obtained in the field, an attempt was made to establish equation which describes pole height - circumference relationship for some selected species. Two forms of equations were tried, namely: Y = AXB and Y = A + BX. The exponential form turned out to be of a better fit. The data on pole taper presented in this paper can hopefully throw some light for future compilation of a table on pole dimension and specification for Indonesian wooden pole species and in a derivation of fiber stresses from strength values of wooden poles.